Work Ability, Job Placement, and Organizational Commitment as Determinants of Employee Performance: Evidence from KPP Madya Dua Surabaya - Wibowo, Arif; Sundjoto, Sundjoto; Rahayu, Sri; Fitrianty, Rifda (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research explores how work ability, job placement, and organizational commitment affect employee performance at KPP Madya Dua Surabaya, a public tax office under Indonesia’s Directorate General of Taxes. Amid increasing expectations for transparency, accountability, and service quality in public organizations, human resources are a central factor in institutional success. A quantitative causal approach was applied, collecting data from 97 employees via structured questionnaires assessing technical, conceptual, and social skills, job-role alignment, and organizational identification, involvement, and loyalty. Multiple linear regression was used to evaluate both individual and combined effects on employee performance. Results indicate that employees’ work ability significantly enhances performance by enabling them to handle complex tasks, leverage their knowledge efficiently, and adapt to organizational and technological changes. Job placement that aligns competencies with roles further boosts performance by promoting efficiency, creativity, and task accuracy. High organizational commitment, demonstrated through identification with organizational goals, pride, engagement, and loyalty, increases motivation and sustained effort, improving performance outcomes. The simultaneous analysis confirms that the interplay of abilities, proper placement, and commitment substantially drives performance, emphasizing the importance of integrated human resource management strategies. These findings provide practical guidance for training, precise assignment of roles, and fostering a motivating organizational culture, while offering a basis for future studies to investigate additional determinants of employee performance in public institutions.